Self-healing properties and environmental evaluation of asphalt mixtures containing steelmaking waste - Fan Zhang; Aimin Sha; Yangsen Cao; Baowen Lou; Wentong Wang; Ruimeng Song (Journal of Traffic and Transportation Engineering (English ed. Online))
Environmental pollution and resource shortages are the two most urgent issues in current society. Using steel slag as aggregates in pavement construction is promising in reducing the exploitation of non-renewable resources. Meanwhile, steel slag, as an excellent microwave-absorbing material, can accelerate the self-healing properties of the pavement. This study aims to explore a value-added development of the asphalt mixture containing steel slag to improve its self-healing properties. For this purpose, the absorbing properties of steel slag were firstly explained based on SEM, X-RD, and X-RF. Then, thermal conductivity, self-healing, and road performance were tested. Finally, the feasibility of replacing aggregates with steel slag was assessed based on environmental evaluation and economic benefits. Results indicated that the porous structure and metal elements of steel slag make it have excellent microwave heating (MH) capacity. The high-temperature stability and water stability of steel slag asphalt mixtures (SSAM) can improve by 60.76% and 5.97%, respectively, while there is a downward trend in low-temperature crack resistance. Besides, asphalt mixtures with 80% steel slag content performed excellent thermal conductivity and healing properties efficiency, which exhibited the maximum thermal parameter (1.56 W/(m·K)), healing index (92.8%), and healing level (63.7%). Based on the purpose of self-healing, 80% replacement of steel slag by volume is recommended. The comprehensive evaluation results on environmental pollution and economic benefits show that using steel slag as aggregates is highly feasible.